2023
DOI: 10.1093/oncolo/oyac261
|View full text |Cite
|
Sign up to set email alerts
|

Combining Sunitinib and Bevacizumab for the Management of Advanced Renal Cell Carcinoma: A Phase I/II Trial

Abstract: Background Tyrosine kinase inhibitors remain a cornerstone in managing metastatic clear cell renal cell carcinoma (RCC). The 4 weeks on/2 weeks off intermittent sunitinib schedule could result in rebound angiogenesis and tumor progression in the 2-week rest period. We propose using bevacizumab during this period for continuous antiangiogenic effects. Method This was a phase I/II study of patients with advanced clear cell RCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The combination of bevacizumab and cediranib, a VEGFR TKI, has demonstrated potent additive antitumor effects against various advanced solid tumors, indicating that targeting the same angiogenic pathway is not redundant [ 12 , 26 ]. Multiple studies have shown a significant antitumor effect of combining bevacizumab and sunitinib in renal cell carcinoma, with manageable increased toxicity [27] , [28] , [29] , [30] . Consistent with these findings, our study revealed excellent synergistic antitumor activity when combining bevacizumab and anlotinib in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of bevacizumab and cediranib, a VEGFR TKI, has demonstrated potent additive antitumor effects against various advanced solid tumors, indicating that targeting the same angiogenic pathway is not redundant [ 12 , 26 ]. Multiple studies have shown a significant antitumor effect of combining bevacizumab and sunitinib in renal cell carcinoma, with manageable increased toxicity [27] , [28] , [29] , [30] . Consistent with these findings, our study revealed excellent synergistic antitumor activity when combining bevacizumab and anlotinib in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been studies of alternating TKIs with bevacizumab, a monoclonal antibody that targets VEGF. A phase I/II trial of patients with advanced clear cell RCC tested the standard 4 weeks on, 2 weeks off sunitinib regimen with the addition of bevacizumab on Day 29 of each sunitinib cycle 30 . The rationale behind this treatment regimen was that the 2‐week rest period of standard sunitinib therapy could result in rebound angiogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I/II trial of patients with advanced clear cell RCC tested the standard 4 weeks on, 2 weeks off sunitinib regimen with the addition of bevacizumab on Day 29 of each sunitinib cycle. 30 The rationale behind this treatment regimen was that the 2‐week rest period of standard sunitinib therapy could result in rebound angiogenesis and tumor progression. As was the case with our study, this study closed prematurely due to poor accrual but in the 25 patients recruited, a median PFS was reported to be 16.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…RCCs are generally divided into five subtypes: clear cell, papillary, chromophobe, collecting duct, and unclassified, among which the first three constitute the majority of RCCs ( Truong and Shen, 2011 ). Although advances in the medical and surgical management of RCCs have been made ( Rini et al, 2009 ; Bazarbashi et al, 2023 ), the outcomes associated with the tumor remain relatively poor ( Badran et al, 2020 ). Additionally, differentiating between different subtypes of RCC is still difficult.…”
Section: Aberrant Expression Of Claudins In Renal Cell Carcinomasmentioning
confidence: 99%